2004
DOI: 10.1196/annals.1309.059
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immune Regulation toward Disease‐Associated Antigens: Results of Phase I Clinical Trials in Crohn's Disease and Chronic Hepatitis

Abstract: Oral immune regulation is an immune response toward orally administered antigens, and is a balance between several types of responses. Recent studies in animal models have shown that antiviral immunity and the immune response toward colonic proteins can be modulated by oral feeding of these antigens. The effect of oral immune regulation on the outcome of various immune-mediated processes, including infectious, inflammatory, and neoplastic entities, has been the subject of much research and debate in recent yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These studies showed that oral feeding in both Crohn's disease (CD) and ulcerative colitis (UC) tends to prime and not to tolerize both T‐ and B‐cell responses 1, 2. Therefore, it stands to reason that 2 clinical treatment trials for CD (oral application of autologous colonic mucosal cells3 or autologous colon‐extracted proteins2 for moderate to severe disease activity) failed to show convincing evidence for effectiveness of oral tolerance therapy in IBD.…”
mentioning
confidence: 99%
“…These studies showed that oral feeding in both Crohn's disease (CD) and ulcerative colitis (UC) tends to prime and not to tolerize both T‐ and B‐cell responses 1, 2. Therefore, it stands to reason that 2 clinical treatment trials for CD (oral application of autologous colonic mucosal cells3 or autologous colon‐extracted proteins2 for moderate to severe disease activity) failed to show convincing evidence for effectiveness of oral tolerance therapy in IBD.…”
mentioning
confidence: 99%
“…Mucosal autoantigen administration is a double-edge sword and may lead not only to regulatory and protective immunity, but also to pathogenic, tissue-destructive immunity and exacerbation of autoimmune disease [4,67]. Oral antigen exposure not only induces suppressive mechanisms but also actives immune responses that are protective, mainly to normal flora [68].…”
Section: Is Oral Tolerance Mediated By a Local Or A Systemic Effect? mentioning
confidence: 99%
“…Antigen-specific therapy is a physiologic means to manipulate immune responses, is nontoxic, and can be administered on a chronic basis [3]. With the understanding that oral exposure to antigens in the bowel results in an active immune response, antigen-specific therapy seems an attractive approach for immunotherapy toward antigens present in the gut mucosa, where they can be dealt with in a noninjurious or noninflammatory immunologic environment [1,4]. As a method for activating specific immune cells, antigen-specific therapy can serve as an immunotherapeutic against tumors and infectious agents [4 -7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to exploit these mechanisms as potential clinical therapy, investigators have used oral tolerance strategies with success to inhibit undesirable immune responses in mouse models of human diseases, including multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease, autoimmune uveitis, type‐1 diabetes, and transplant rejection (1). These animal studies paved the way for subsequent clinical trials in autoimmune diseases, which yielded mixed results (9–14). Conceptually, oral immune tolerance might be better suited for solid organ transplantation than for autoimmunity, because the antigens are defined and administration can be timed to the transplant.…”
mentioning
confidence: 99%